Observasi pelayanan publik pada pendampingan masa orientasi studi dan pengenalan kampus mahasiswa baru - Windiasari, Fica Afria (Maliki Interdisciplinary Journal, 2023)
This study is an implementation of observing mentoring activities for new students in the Islamic Banking Family (IBF) committee organized by HMPS Sharia Banking at the Faculty of Economics, UIN Maulana Malik Ibrahim. This research uses field observation methods to understand the dynamics of communication and interaction in activities. Observation results showed that even though the participants and companions had been divided into groups, there were still inhibiting factors such as lack of participant enthusiasm, delays in completing tasks, and imperfect location preparation. However, the companion has an important role as a direct liaison between the committee and participants, providing direction, information and helping to complete assignments. Therefore, effective coordination, clear job descriptions, good time management, and strong communication and cooperation between committee members can reduce inhibiting factors. This research emphasizes the importance of good organizational communication and the important role of companions in achieving activity goals, highlighting the need for individuals who have strong interpersonal skills to embrace and support group members well. Keywords: new student mentoring, organizational communication, group interaction